COVID-19 and the Gut Microbiome: More than a Gut Feeling - van der Lelie, Daniel (mSystems, 2020)
Due to its fundamental role in the induction, training, and function of the immune system, it is critical to include characterizations of the gut microbiome in clinical trials and studies that aim to broaden our understanding of coronavirus disease 2019 (COVID-19). Understanding the “gut-lung axes,” where gut microbiome composition influences the lung’s susceptibility to viral infections and viral infections of the lung alter gut microbiome composition toward proinflammatory functional dysbiosis, will be critical in addressing COVID-19, including disease progression, the importance of preexisting conditions, and the risk for developing complications. These insights may further help to develop better intervention strategies for COVID-19 and other diseases caused by respiratory viruses.